2010
DOI: 10.1007/s10384-009-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the XLRS1 gene in Thai families with X-linked juvenile retinoschisis

Abstract: A novel p.D126G mutation appeared to be associated with a severe phenotype with vitreous hemorrhage developing in infancy. Both intra- and interfamilial clinical variabilities were recognized in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…To date, this is the first report of the 573delG mutation in the Chinese population, which widens the mutational spectrum of RS1 and is expected to help with diagnosis of this rare genetic disease XLRS in Asians. This identified mutation is present in the hotspot region at amino acid position 192, belonging to the highly conserved discoidin motif of retinoschisin protein, which supports the notion that this domain has functional significance in cell-tocell adhesion (9). Our results are in agreement with previous findings reported in an Australia population by Hewitt et al (10).…”
Section: Discussionsupporting
confidence: 83%
“…To date, this is the first report of the 573delG mutation in the Chinese population, which widens the mutational spectrum of RS1 and is expected to help with diagnosis of this rare genetic disease XLRS in Asians. This identified mutation is present in the hotspot region at amino acid position 192, belonging to the highly conserved discoidin motif of retinoschisin protein, which supports the notion that this domain has functional significance in cell-tocell adhesion (9). Our results are in agreement with previous findings reported in an Australia population by Hewitt et al (10).…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that retinoschisis in this family is a necessary consequence to optic disc anomalies, but with morphologic variants. Noteworthy, the proband III:8 and patient III:1 were originally misdiagnosed as inherited retinoschisis, which is often juvenile onset, X-linked with mutations in the retinoschisin ( RS1 , MIM: 312700) gene, and involves maculae 15 19 . Macular retinoschisis can also occur in the condition of glaucoma with progressively enlarged excavation 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the high number of RS1 mutations, several studies investigated a possible correlation between genotype and phenotype. Even though some reports describe a correlation between specific variations and the severity of clinical phenotype (22,23), the majority of published studies found that XLRS patients had relatively uniform clinical manifestations, although with great intra-familial variation in age at onset and progression (1,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%